Strengthening pharmacovigilance systems through post-vaccination surveillance in Nigeria: A narrative review - Umar, Abbas B.; Ibrahim, Adamu M.; Yusuf, Abduljalal N.; Zubairu, Mubarak; Ahmed, Mohamed M.; Lucero-Prisno III, Don E. (Narra Sains Indonesia, 2025)
Immunization remains a vital pillar of Nigeria’s public health agenda, significantly reducing the burden of vaccine-preventable diseases. However, the success of immunization programs hinges not only on vaccine access and delivery but also on robust post-vaccination surveillance systems that ensure vaccine safety and foster public confidence. In Nigeria, post-vaccination pharmacovigilance, led by the National Agency for Food and Drug Administration and Control (NAFDAC), faces critical challenges, including underreporting of adverse events following immunization (AEFIs), inadequate healthcare worker training, infrastructural limitations, and the widespread influence of misinformation. These systemic weaknesses threaten to undermine vaccine confidence, particularly in underserved and rural areas. The aim of this study was to examine the current state of Nigeria’s post-vaccination surveillance infrastructure, highlighting gaps in AEFI reporting and data management. Drawing on global best practices and successful models from other low- and middle-income countries (LMICs), this study proposes a set of strategic interventions to strengthen pharmacovigilance. These include the adoption of digital and mobile health technologies, capacity building for healthcare providers, community engagement, and integration of artificial intelligence in safety signal detection. This study underscores the urgency of regulatory reform and private sector inclusion, advocating a holistic and sustainable approach to vaccine safety monitoring. By reinforcing pharmacovigilance systems, Nigeria can build public confidence, improve vaccine uptake, and enhance the overall effectiveness of its national immunization program.